Research Paper on the Role of Work and Industrial/Organizational Psychologist Using Change Management, Leadership: Examining the Role of Mental Possession in Successful Organizational Change Management (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Authoritative change management is characterized as an organized way to deal with progressing a specific hierarchical entity from its present state to an ideal future state. The motivation behind this examination is to expand hypothetical and down to earth learning of change management in organizations as far as forerunners of effective change by utilizing the hypothesis of mental possession. The recognized regular forerunners of a fruitful progress are a reasonable vision, dynamic support, viable and dependable correspondence, status for change, and showing of feasible advancement in change. Additionally, top management backing and duty are vital for achievement in hierarchical change. In any case, there is a hole in clarifying why these specific forerunners add to effective change. Hence, the goal in this doctoral research is to propel comprehension of the predecessors of fruitful hierarchical progress toward the ideal state and all the while to deliver the beneficial outcomes of change management inside arranged change. The hypothesis of mental possession in organizations encourages this commitment. As a perspective, mental possession is that state where an individual feels as though the objective of proprietorship (material or irrelevant in nature) or a bit of it is hisher (i.e., It is mine). The centre of mental proprietorship is the inclination of possessiveness and being mentally attached to an article. Observationally, the investigation looks at the change arranged, actualized, and finished inside a worldwide assembling organization. Research material was gathered as an activity research venture from 2004 through 2007 and investigated later as a contextual analysis. An apparatus for positive change management, grateful request, was utilized for arranging and executing the change. The discoveries of the investigation demonstrate that understanding the mental possession system includes comprehension of change management, especially forerunners of fruitful change inside the setting of arranged change.